Low power wide area network (LPWAN) protocols: Enablers for future wireless networks - Ala’ Khalifeh; Aws Al-Qaisi; Khaled Aldahdouh; Waleed T. Al-Sit; Ayat AL Olaimat; Sahel Alouneh; Khalid A. Darabkh (Results in Engineering)
Low Power Wide Area Network (LPWAN) protocols are considered the enablers for the future of the Internet of Things (IoT) enabled networks. Examples of these networks are Internet of Things-Wireless Sensor Networks (IoT-WSNs), and Industrial Internet of Things (IIoT). Many LPWAN protocols were introduced to meet the requirements of IoT-enabled networks in future wireless networks such as the Fifth Generation (5G) and beyond communication systems. Long transmission distance, power efficiency and low latency with reasonable bit rate are the most requirements of these networks. In this paper, the emerged wireless protocols, which are considered the potential infrastructures for the deployment of IoT-enabled networks such as IIoT and WSNs are presented. Particularly, Long Range Wireless Area Networks (LoRaWAN), Sigfox, Narrow Band-Internet of Things (NB-IoT), Long Term Evolution for Machines (LTE-M) and Wireless Fidelity (Wi-Fi) HaLow (802.11ah). The Physical and Media Access Control (MAC) layers of these protocols, and how IoT networks can be deployed utilizing these protocols are discussed. These protocols then are compared in terms of their potential for meeting the stringent requirements of IoT-enabled networks in terms of power consumption, network topology, communication range, spectrum utilization, data rate, channel bandwidth, and Quality of Service (QoS). Furthermore, other important technical details that can act as determining factors for adopting these protocols such as Time on Air, security, and deployment cost are discussed.